THE ROLE OF PLATELET CONCENTRATION TRANSFUSION ON THE CORRELATION BETWEEN PLATELET NUMBER AND MAXIMUM AMPLITUDE WITH BLEEDING VOLUME POST CARDIOPULMONARY BYPASS - Ryan Bayusantika Ristandi; Nida Suraya; Leni Lismayanti; Sylvia Rachmayati (Indonesian Association of Clinical Pathologist and Medical laboratory, 2018)
Postoperative heart patients with Cardiopulmonary Bypass (CPB) are at risk of excessive bleeding. Excessive bleeding is mainly due to thrombocytopenia and platelet dysfunction. The volume of post-CPB bleeding without the administration of platelet concentrate correlates well with platelet count and Maximum Amplitude (MA). The administration of platelet concentrate in thrombocytopenia and platelet dysfunction post CPB may affect the correlation of platelet count and MA which affects the volume of bleeding. The purpose of this research was to know the role of transfusion of platelet concentration post-CPB on the correlation between platelet number and MA with the volume of bleeding. The analytical observational analytic test with the cross-sectional design was conducted on secondary data from September 2015 to March 2016. A total of 44 postoperative heart patients CPB monitored up to four hours in the room Cardiac Intensive Care Unit (CICU) Dr. HasanxSadikin HospitalxBandung. The platelet count was negatively correlated with bleeding volume (r = -0.157, p = 0.308) and the MA was negatively correlated (very weak) with bleeding volume (r = -0.171, p = 0.266). The post-CPB platelet concentrate concentration led to better patient hemostasis, as evidenced by the majority of platelet counts (97.7%)> 100,000/mm3 and MA (84%)x≥x50xmm. The post-CPB platelet concentrate causes a negative (very weak) correlation between platelet count and MA with bleeding volume